answersLogoWhite

0


Best Answer

The easiest way to solve this system of equations is to solve for a variable in one of the equations. In the second equation, y = 3x. This can be substituted into the first equation:

y = -4x - 7;

3x = = -4x - 7;

7x = -7;

x = -1.

Since we have determined that x equals -1, we can then substitute -1 into either equation to find our corresponding y-value. Thus:

y = 3x;

y = 3(-1)

y = -3.

Thus, the solution to this system of equations is (-1, -3).

User Avatar

Wiki User

โˆ™ 2010-02-27 23:16:50
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.75
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1050 Reviews

Add your answer:

Earn +20 pts
Q: Solve by substitution y equals -4x - 7 and y equals 3x?
Write your answer...
Submit
Still have questions?
magnify glass
imp
People also asked